Fungal diversity and drug susceptibility of the oral mycobiome of domestic dogs - Esquivel, Brooke D.; Rouse Salcido, Elisa M.; Schweiker, Allison M.; Holder, Brandon L.; KuKanich, Butch; KuKanich, Kate S.; White, Theodore C. (Frontiers in Veterinary Science, 2023)
The purpose of this study was to characterize the variety and diversity of the oral mycobiome of domestic dogs and to identify the commensal and potentially pathogenic fungi present. Two hundred fifty-one buccal swabs from domestic dogs were obtained and struck onto a chromogenic fungal growth medium that distinguishes between fungal species based on colony color and morphology. After isolating and harvesting single colonies, genomic DNA was extracted from pure cultures. PCR was used to amplify a fungal-specific variable rDNA region of the genome, which was then sent for sequencing. Sequencing results were input into the NCBI BLAST database to identify individual components of the oral mycobiome of tested dogs. Of the 251 dogs swabbed, 73 had cultivable fungi present and 10 dogs had multiple fungal species isolated. Although the dogs did not show signs of oral infections at the time, we did find fungal species that cause pathogenicity in animals and humans. Among fungal isolates, Malassezia pachydermatis and species from the genus Candida were predominant. Following fungal isolate identification, antifungal drug susceptibility tests were performed on each isolate towards the medically important antifungal drugs including fluconazole, ketoconazole, and terbinafine. Drug susceptibility test results indicated that a large number of isolates had high MIC values for all three drugs. Exploring the oral mycobiome of dogs, as well as the corresponding drug susceptibility profiles, can have important implications for canine dental hygiene, health, and medical treatment. Identifying the microorganisms within the canine mouth can illustrate a common pathway for fungal pathogens of One Health concern to spread from our canine companions to humans.